NCI: looking at solute/solvent interactions. (31st August 2021) - Chaudret, R; Narth, C; Lugo, R; Mougin, P; Hemptinne, J-C de; Toulhoat, H; Contreras-García, J
Abstract: Understanding solvation interactions is a key problem for many industrial fields: from pharmaceutical to material sciences. From a quantum mechanical viewpoint, two main difficulties arise: firstly, solvation takes place through weak interactions (hydrogen bonds, van der Waals interactions), which are inherently difficult to describe. Secondly, solvation properties are dynamic in nature, which means a proper statistical averaging is required to reproduce experimental properties. In this contribution, we dwell on the analysis of solute–solvent interactions by means of the averaged-NCI index, derived from an MD averaged picture of the electron density in the system. Firstly, we show how the approach enables to distinguish static vs labile and strong vs weak hydrogen bonds. Then, by means of this approach we are able to characterize the fact that the strength of hydrogen bonds with water solvent remains similar upon branching for aliphatic alcohols. On the contrary large differences have been observed between aliphatic alcohols and phenol derivatives. This statistical analysis of interactions is expected to be useful in the derivation of microscopic parameters for solute/solvent interactions.